A Study of The Behavior of Non-Commissioned Police Students In Character and Discipline Development at the Central Kalimantan Regional Police SPN - Hendrik Kristanto; Siti Khotimah; Elingsih Elingsih; Asep Solikin; Heru Nurohman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Character building and discipline are the primary foundations of police education, as the behavioral quality of student non-commissioned officers (NCOs) is an indicator of their readiness as law enforcement officers with integrity and professionalism. This study aims to analyze the behavior of student non-commissioned officers (NCOs) during the character and discipline building process at the Central Kalimantan Regional Police's National Police Service (SPN), and to identify influencing factors. The research approach employed was a descriptive qualitative method, with NCOs as the subjects. Data were collected through in-depth interviews and observations of student behavior during learning activities, physical training, and character development within the SPN environment. The results indicate that student behavior in the context of character and discipline building is influenced by two main factors: internal factors (personal motivation, moral values, and awareness of responsibility) and external factors (instructor role models, the development system, and police organizational culture). Effective character building is characterized by the integration of role models, time discipline, collective responsibility, and the internalization of the Tribrata and Catur Prasetya values. Therefore, police education at the Central Kalimantan Regional Police's National Police Service (SPN) plays a strategic role in developing prospective police officers with character, high discipline, and readiness to carry out their duties professionally.